Upaya Pelestarian Tradhisi Ruwah Dusun Pacet Made Desa Pacet Kecamatan Pacet Kabupaten Mojokerto - Rizka Alfianita; Sukarman Sukarman (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This study aims to explore the efforts of the Pacet Made community in preserving the "Ruwah Dusun" tradition amidst changing times. The Ruwah tradition, an annual ritual held in the month of Ruwah or Sha’ban before Ramadan, holds profound philosophical and spiritual meaning. This research employs a descriptive qualitative method through interviews, observations, and data analysis using Nahak’s theory (2019:72). The findings reveal that despite modernization and globalization influencing the form and meaning of this ritual, the Pacet Made community remains steadfast in their cultural roots with various adaptation efforts, such as innovation in tradition, syncretization with religious values, and socialization to the younger generation. Preservation efforts are carried out by strengthening cultural education, documenting and publishing, utilizing information technology, and developing derivative products from the Ruwah tradition. Through this research, it is hoped that the Ruwah tradition in Pacet Made Village will not only be preserved but also inspire and empower the community in facing the challenges of the times.